Overcurrent protection element

By improving the microstructure of polymer substrates and using carbon black as conductive filler, the durability problem of existing overcurrent protection elements under high cycle count and high voltage conditions is solved, and high resistance stability and durability are achieved.

CN119673594APending Publication Date: 2025-03-21POLYTRONICS TECH CORP
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311351894.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-20
Filing Date
2023-10-18
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing overcurrent protection elements still have room for improvement in durability, especially under high cycle count and high voltage conditions, which are prone to burn and have poor resistance stability.

Method used

By improving the microstructure characteristics of the polymer substrate, including reducing the fractal dimension of the spherical crystal surface and controlling the spherical crystal radius, the thermistor layer of the overcurrent protection element is more stable. At the same time, carbon black is used as the conductive filler to avoid adding cermet materials to improve durability.

Benefits of technology

The overcurrent protection element is achieved with high durability and resistance stability under high cycle count and high voltage conditions, and can withstand 36V/33A cycle life tests 6000 times without burning.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673594A_ABST
    Figure CN119673594A_ABST
Patent Text Reader

Abstract

An over-current protection element comprises an electrode layer and a thermistor layer. The electrode layer has an upper metal layer and a lower metal layer. The thermistor layer contacts the upper metal layer and the lower metal layer and is stacked between the upper metal layer and the lower metal layer. The thermistor layer has a positive temperature coefficient characteristic and contains a high-molecular polymer base material and a conductive filler. The high-molecular polymer base material contains a fluorine-containing polymer, the fluorine-containing polymer has a plurality of spherocrystals, and the fractal dimension of the surface of each spherocrystal is lower than 12.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an overcurrent protection element, and more particularly to an overcurrent protection element with high durability. Background Art

[0002] The resistance of existing conductive composite materials with positive temperature coefficient (PTC) characteristics is very sensitive to changes in specific temperature. They can be used as materials for current sensing elements and are currently widely used in overcurrent protection elements or circuit elements. Specifically, the resistance of PTC conductive composite materials can be maintained at an extremely low value at normal temperature, allowing the circuit or battery to operate normally. However, when the circuit or battery has an overcurrent (over-current) or overtemperature (over-temperature) phenomenon, its resistance value will instantly increase to a high resistance state (at least 10 4 Ω or more), which is called a trip, and the overcurrent is cut off to protect the battery or circuit components.

[0003] The most basic structure of an overcurrent protection element is composed of a PTC material layer and metal electrodes attached to both sides thereof. The PTC material layer includes at least a substrate and a conductive filler. The substrate is composed of a polymer, and the conductive filler is dispersed in the polymer as a conductive path. In recent years, considering the demand for high temperature overheating protection in the automotive market, polymer substrates often use polymers with high melting points as their main components, such as polyvinylidene fluoride. Traditionally, in order to effectively improve the service life (i.e. durability) of the above-mentioned overcurrent protection element under high voltage, other additives need to be added. However, the addition of other additives often complicates the formulation design. For example, the compatibility of the additive with the polymer and the conductive filler must be considered in the selection of the additive. Moreover, after the additive is selected, the ratio of the polymer and the conductive filler needs to be precisely adjusted to maintain good electrical properties. In addition, in order to respond to the rapidly changing industry needs, the formulation is often subject to improvement. With each additional chemical composition, the complexity of future improvements will increase sharply.

[0004] It should also be understood that in order to use space efficiently and in line with the policy of energy conservation and carbon reduction, component miniaturization is the current trend. However, the defects in various electrical characteristics are easily aggravated as the size of the overcurrent protection component becomes smaller. Traditionally, even if the physical and chemical properties of the polymer substrate itself are to be improved, it is often difficult to make a significant breakthrough due to the problem of defect amplification caused by the small size of the component.

[0005] In summary, there is still considerable room for improvement in the durability of existing overcurrent protection components. Summary of the invention

[0006] The present invention provides an overcurrent protection element with high durability. The overcurrent protection element includes an electrode layer and a thermistor layer. The electrode layer is used as a layer for electrical connection, and the thermistor layer includes a polymer substrate and a conductive filler, and is used as a layer that exhibits positive temperature coefficient characteristics. The present invention improves the surface complexity (i.e., the fractal dimension of the spherulite surface) and size (i.e., the spherulite radius) of the microstructure of the polymer substrate, so that the overcurrent protection element can withstand a high cycle number and high voltage cycle life test without burning, and the thermistor layer therein can be made thinner.

[0007] According to one embodiment of the present invention, an overcurrent protection element includes an electrode layer and a thermistor layer. The electrode layer has an upper metal layer and a lower metal layer. The thermistor layer contacts the upper metal layer and the lower metal layer and is stacked therebetween. The thermistor layer has a positive temperature coefficient characteristic and includes a polymer substrate and a conductive filler. The polymer substrate includes a fluorine-containing polymer, and the fluorine-containing polymer has a plurality of spherulites, and the fractal dimension of the surface of each spherulite is less than 12. The conductive filler is dispersed in the polymer substrate to form a conductive path of the thermistor layer.

[0008] According to some embodiments, the fractal dimension of each spherulite surface is between 7 and 12.

[0009] According to some embodiments, each of the spherulites has a spherulite radius greater than

[0010] According to some embodiments, the spherulite radius is between and between.

[0011] According to some embodiments, based on 100% by volume of the thermistor layer, the fluorine-containing polymer accounts for 55% to 68%.

[0012] According to some embodiments, the fluorine-containing polymer is selected from the group consisting of polyvinylidene fluoride, polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, perfluoroalkylene-modified tetrafluoroethylene, poly(chlorotri-fluorotetrafluoroethylene), difluoroethylene-tetrafluoroethylene polymer, tetrafluoroethylene-perfluorodioxole copolymer, difluoroethylene-hexafluoropropylene copolymer, difluoroethylene-hexafluoropropylene-tetrafluoroethylene terpolymer, and any combination thereof.

[0013] According to some embodiments, the fluorine-containing polymer consists of polyvinylidene fluoride and polytetrafluoroethylene.

[0014] According to some embodiments, based on 100% by volume of the thermistor layer, polyvinylidene fluoride accounts for 56% to 62% and polytetrafluoroethylene accounts for 3% to 5%.

[0015] According to some embodiments, the conductive filler consists of carbon black.

[0016] According to some embodiments, the thickness of the thermistor layer is 0.1 mm to 0.2 mm.

[0017] According to some embodiments, the overcurrent protection element has a top surface area of ​​4 mm 2 Up to 16mm 2 .

[0018] According to some embodiments, the overcurrent protection element has a first resistance jump ratio between 1 and 3. The overcurrent protection element has an initial resistance value; the overcurrent protection element has the first resistance value after being subjected to a 24V / 50A cycle life test for 6,000 cycles and cooled to room temperature; and the first resistance value divided by the initial resistance value is the aforementioned first resistance jump ratio.

[0019] According to some embodiments, the overcurrent protection element has a second resistance jump ratio between 2 and 5. The overcurrent protection element has an initial resistance value; the overcurrent protection element has a second resistance value after being cycled 6000 times in a 30V / 40A cycle life test and cooled to room temperature; and the second resistance value divided by the initial resistance value is the aforementioned second resistance jump ratio.

[0020] According to some embodiments, the overcurrent protection element has a withstand voltage of 36V, whereby the overcurrent protection element does not burn out after undergoing a 36V / 33A cycle life test for 6,000 cycles.

[0021] According to some embodiments, the overcurrent protection element has a third resistance jump ratio between 3 and 9. The overcurrent protection element has an initial resistance value; the overcurrent protection element has a third resistance value after being cycled 6000 times in a 36V / 33A cycle life test and cooled to room temperature; and the third resistance value divided by the initial resistance value is the aforementioned third resistance jump ratio. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A cross-sectional view showing an overcurrent protection element according to an embodiment of the present invention;

[0023] Figure 2 show Figure 1 a top view of an overcurrent protection element; and

[0024] Figures 3 to 5 The graph shows the results obtained by small-angle X-ray scattering (SAXS) analysis.

[0025] The reference numerals are described as follows:

[0026] 10: Overcurrent protection element

[0027] 11: Thermistor layer

[0028] 12: Upper metal layer

[0029] 13: Lower metal layer

[0030] A: Length

[0031] B: Width

[0032] L1, L2, L3, L4, L5, L6: Straight line

[0033] T: Thickness DETAILED DESCRIPTION

[0034] In order to make the above and other technical contents, features and advantages of the present invention more clearly understood, relevant embodiments are given below and described in detail with reference to the accompanying drawings.

[0035] Please refer to Figure 1 , showing the basic state of the overcurrent protection element of the present invention. The overcurrent protection element 10 includes a thermistor layer 11 and an electrode layer. The thermistor layer 11 has an upper surface and a lower surface, and the electrode layer has an upper metal layer 12 and a lower metal layer 13 respectively attached to the upper surface and the lower surface of the thermistor layer 11. In this way, the thermistor layer 11 is physically in direct contact with the upper metal layer 12 and the lower metal layer 13, and is stacked between the two. In one embodiment, the upper metal layer 12 and the lower metal layer 13 can be composed of nickel-plated copper foil or other conductive metals. In addition, the thermistor layer 11 includes a polymer substrate and a conductive filler. The polymer substrate is an insulator that is easily expanded by heat, and the conductive filler is a conductor, whereby the thermistor layer 11 has a positive temperature coefficient characteristic. When the overcurrent protection element 10 is not triggered, the conductive filler is evenly dispersed in the polymer matrix and connected in series to form a conductive channel; when the overcurrent protection element 10 is affected by high temperature, the polymer matrix will expand rapidly, causing the conductive filler particles to be pulled apart from each other, resulting in the truncation of the conductive channel.

[0036] In the present invention, the polymer matrix is ​​composed of a fluorine-containing polymer, and the fluorine-containing polymer can be composed of one or more fluorine-based compounds. More specifically, the fluorine-containing polymer is selected from the group consisting of polyvinylidene fluoride, polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, perfluorocarbon oxide modified tetrafluoroethylene, poly (chlorotri-fluorotetrafluoroethylene), difluoroethylene-tetrafluoroethylene polymer, tetrafluoroethylene-perfluorodioxole copolymer, difluoroethylene-hexafluoropropylene copolymer, difluoroethylene-hexafluoropropylene-tetrafluoroethylene terpolymer and any combination thereof. In one embodiment, the fluorine-containing polymer is composed of polyvinylidene fluoride and polytetrafluoroethylene. The present invention further improves the microstructural features of the fluorine-containing polymer (i.e., the fractal dimension of the spherulite surface and the spherulite radius), so that the overcurrent protection element 10 has obvious improvements in electrical properties.

[0037] It should be noted that the aforementioned fluorine-containing polymer is a semi-crystalline polymer, which means that in terms of the crystal structure, it can be divided into an orderly arranged crystalline region (crystalline region) and a disordered arranged amorphous region (amorphous region). In the crystalline region, the molecular chains of the polymer will first be folded regularly to form the smallest unit of the crystalline structure. Then, these folded molecular chains will further accumulate into lamellae, and finally multiple lamellae will be stacked into spherulites. Accordingly, multiple spherulites can constitute the aforementioned orderly arranged crystalline region in the polymer. With the emergence of fractal mathematics, the complexity of the spherulite surface can be represented by the fractal dimension. The larger the fractal dimension, the greater the complexity of the spherulite surface, that is, the spherulite surface is relatively uneven. On the contrary, the smaller the fractal dimension, the smaller the complexity of the spherulite surface, that is, the spherulite surface is relatively flat. It should be understood that the complexity of the spherulite surface is related to the stability of the spherulite structure, and the reasons that contribute to the stability of the spherulite structure may be, for example, the degree of cross-linking between molecular chains and / or other unexpected physicochemical properties. For example, in a polymer, molecular chains with a high degree of cross-linking will make the structure of the spherulites more stable and form spherulites with a smooth surface, so the present invention controls the fractal dimension of the spherulite surface to be less than 12. When the fractal dimension is less than 12, the multiple spherulites of the fluorine-containing polymer have a smoother surface, and the stability of the spherulite structure is sufficient to perform well in durability tests (see Table 3 below). In one embodiment, the aforementioned fractal dimension is between 7 and 12. In one embodiment, the aforementioned fractal dimension is 7, 8, 9, 10, 11 or 12. In another embodiment, the aforementioned fractal dimension is 7.9, 9.8, 10.9 or 11.6. In addition, the present invention also controls the spherulite radius to be greater than Compared with multiple small spherulites, when multiple large spherulites occupy a specific space, the exposed area (the interface between spherulites or the amorphous area) is more concentrated, so the conductive filler is easier to connect in series to form a conductive channel. ), which can also form large spherulites again during the recrystallization process after triggering, which helps the conductive fillers to quickly connect in series to form a conductive channel, so as to restore the low resistance characteristics of the overcurrent protection element 10. However, it should be noted that the radius of the spherulites should not be too large, otherwise the conductive fillers are prone to be too concentrated (i.e., excessively concentrated at the interface between spherulites or the amorphous region). Therefore, in one embodiment, the spherulite radius is preferably between and In one embodiment, the spherulite radius may be or In another embodiment, the spherulite radius is or The aforementioned fluorine-containing polymer can be modified in its microstructure (i.e., spherulite) by heat treatment, radiation, and / or different polymerization methods. After adjustment, the fractal dimension and spherulite radius of the spherulite surface are analyzed and confirmed by a small angle X-ray scattering (SAXS) instrument.

[0038] In addition, in order to make the overcurrent protection element 10 maintain good triggering characteristics, the volume percentage of the fluorine-containing polymer in the thermistor layer 11 is at least more than half. For example, based on the volume percentage of the thermistor layer 11 being 100%, the fluorine-containing polymer accounts for 55% to 68%. In one embodiment, the volume percentage of the aforementioned fluorine-containing polymer may be 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 67% or 68%. As mentioned above, the fluorine-containing polymer may be composed of polyvinylidene fluoride and polytetrafluoroethylene. In the proportion of the aforementioned fluorine-containing polymer, based on the volume percentage of the thermistor layer 11 being 100%, the polyvinylidene fluoride may be 56% to 62%, and the polytetrafluoroethylene may be 3% to 5%. For example, in one embodiment, based on the volume percentage of the thermistor layer 11 being 100%, the polyvinylidene fluoride is about 58%, and the polytetrafluoroethylene is about 4%. In another embodiment, in order to improve thermal stability or meet other requirements, the content of polytetrafluoroethylene can be increased, for example, based on the volume percentage of the thermistor layer 11 being 100%, the polyvinylidene fluoride is 56%, and the polytetrafluoroethylene is 5%.

[0039] As for the conductive filler, the conductive filler of the present invention is composed of carbon black. That is to say, the conductive filler of the present invention is only composed of carbon black, and does not contain metal ceramic materials that can also be used as conductive paths. The aforementioned metal ceramic materials are selected from the group consisting of tungsten carbide, titanium carbide, vanadium carbide, zirconium carbide, niobium carbide, tantalum carbide, molybdenum carbide, hafnium carbide, titanium boride, vanadium boride, zirconium boride, niobium boride, molybdenum boride, hafnium boride, zirconium nitride and any combination thereof. If the conductive filler contains these metal ceramic materials, the overcurrent protection element 10 is easy to burn out in the subsequent durability test.

[0040] Please continue to refer to Figure 1 and Figure 2 . It should also be noted that, through the aforementioned improvements, the present invention can make the size (i.e., length, width, and thickness) of the overcurrent protection element 10 extremely small while still maintaining good durability. Traditionally, in order to ensure the voltage resistance of the element, the yield rate in the process, or other element performance, the thickness of the thermistor layer is made to be at least about 0.28 mm. In contrast, in the present invention, the thickness of the thermistor layer 11 can be greatly reduced while maintaining good durability. Figure 1 As shown, the thickness T of the thermistor layer 11 is 0.1mm to 0.2mm, for example 0.1mm, 0.11mm, 0.12mm, 0.13mm, 0.14mm, 0.15mm, 0.16mm, 0.17mm, 0.18mm, 0.19mm or 0.2mm. In this way, the aforementioned extremely thin thermistor layer 11 can be combined with electrode layers of different thicknesses to produce more overcurrent protection elements 10 with thickness specifications that meet the requirements. Relatively speaking, the electrode layer has a higher degree of freedom in thickness selection. In addition, the overcurrent protection element 10 has a length A and a width B, and the area "A×B" is also equal to the area of ​​the thermistor layer 11. The thermistor layer 11 may have a top view area of ​​4mm depending on the product model. 2 Up to 16mm 2 For example, the area "A x B" can be 2 x 2 mm 2 , 2.3×2.3mm 2 , 2.5×3mm 2 , 2.8×3.5mm 2 , 3×4mm 2 or 4×4mm 2 It should be understood that the overcurrent protection device 10 of the present invention has the same effect when applied to the above-mentioned sizes. Moreover, the overcurrent protection device 10 can be processed into a common component type in the industry according to needs, such as a surface-mount device (SMD), an axial-leaded device (ALD), a radial-leaded device (RLD) or other types of components.

[0041] Based on the above formula and size, the overcurrent protection element 10 of the present invention further includes better resistance stability and durability. The durability test is described below. The durability test is performed using three cycle life tests (hereinafter referred to as the first cycle life test, the second cycle life test, and the third cycle life test). The cycle life test is to apply a specific power for 10 seconds and then turn it off for 60 seconds as one cycle.

[0042] In the first cycle life test, the overcurrent protection element 10 has a first resistance jump ratio between 1 and 3. More specifically, the overcurrent protection element 10 has an initial resistance value, and has a first resistance value after 6000 cycles of the 24V / 50A cycle life test and cooling to room temperature. The aforementioned first resistance jump ratio is defined as the ratio obtained by dividing the first resistance value by the initial resistance value. The first resistance jump ratio of a conventional overcurrent protection element can usually be as high as 5 or more, which is much higher than the first resistance jump ratio of the overcurrent protection element 10 of the present invention, indicating that the overcurrent protection element 10 of the present invention has better resistance stability.

[0043] In the second cycle life test, the overcurrent protection element 10 has a second resistance jump ratio between 2 and 5. More specifically, the overcurrent protection element 10 has an initial resistance value, and has a second resistance value after 6000 cycles of the 30V / 40A cycle life test and cooling to room temperature. The aforementioned second resistance jump ratio is defined as the ratio obtained by dividing the second resistance value by the initial resistance value. The second resistance jump ratio of a conventional overcurrent protection element can usually be as high as 10 or more, which is much higher than the second resistance jump ratio of the overcurrent protection element 10 of the present invention, indicating that the overcurrent protection element 10 of the present invention has better resistance stability.

[0044] In the third cycle life test, the overcurrent protection element 10 has a third resistance jump ratio, which is between 3 and 9. More specifically, the overcurrent protection element 10 has an initial resistance value, and has a third resistance value after 6000 cycles of the 36V / 33A cycle life test and cooling to room temperature. The aforementioned third resistance jump ratio is defined as the ratio obtained by dividing the third resistance value by the initial resistance value. It should be noted that in the third cycle life test, the conventional overcurrent protection element will burn out due to excessive voltage, so the third resistance value cannot be measured. In other words, compared with conventional overcurrent protection elements, the overcurrent protection element 10 of the present invention has excellent high voltage resistance.

[0045] To more specifically illustrate the technical content of the present invention, the following Tables 1 to 3 are further discussed with actual verification data.

[0046] Table 1. Ratio of thermistor layer (vol%)

[0047]

[0048] Table 2. Microstructural characteristics of polymer substrates

[0049]

[0050] As shown in Table 1, the formula composition of the thermistor layer 11 is shown in volume percentage. In this experiment, the thermistor layer 11 is composed of polyvinylidene difluoride (PVDF), polytetrafluoroethylene (PTFE), magnesium hydroxide (Mg(OH) 2 ) and carbon black (Carbon Black, CB). Polyvinylidene fluoride and polytetrafluoroethylene together form the high molecular polymer matrix of the thermistor layer 11, and carbon black is dispersed in the high molecular polymer matrix as a conductive path. Magnesium hydroxide is used as a flame retardant and can also neutralize the hydrofluoric acid (HF) generated when polyvinylidene fluoride is cracked. In addition, as mentioned above, the conductive filler used in the formula is only composed of carbon black, and no metal ceramic material is added.

[0051] The manufacturing process of the overcurrent protection element of Examples E1 to E4 and Comparative Examples C1 to C2 of the present invention is described as follows. First, based on the formula presented in Table 1, the materials in the formula are added to a twin-screw mixer produced by HAAKE for mixing. The mixing temperature is set to 215°C, the premixing time is 3 minutes, and the mixing time is 15 minutes. After mixing, a conductive polymer can be obtained and a hot press is used at 210°C and 150kg / cm 2 The sheet was then cut into squares of about 20 cm x 20 cm. Then, the hot press was used again at 210°C and 150 kg / cm 2The two nickel-plated copper foils are pressed onto the two sides of the conductive polymer sheet with a pressure to form a plate with a three-layer structure. Finally, a punch is used to punch out a plurality of chips from the plate, and these chips are overcurrent protection elements. The length A, width B and thickness T of each chip are 3 mm, 4 mm and 0.13 mm, respectively. Then, the chips prepared in the embodiments and comparative examples are heat treated. In comparative example C1, the chip is treated at a temperature of 80°C for 4 hours; in comparative example C2, the chip is treated at a temperature of 100°C for 4 hours; in embodiment E1, the chip is treated at a temperature of 120°C for 3 hours; in embodiment E2, the chip is treated at a temperature of 140°C for 2 hours; in embodiment E3, the chip is treated at a temperature of 160°C for 2 hours; and in embodiment E4, the chip is treated at a temperature of 170°C for 2 hours. Through the aforementioned different heat treatment conditions, the surface complexity and size of the spherulites in the fluorine-containing polymer can be adjusted, and are listed in Table 2 above after analysis by a small-angle scattering instrument.

[0052] Please refer to Table 2 and Figures 3 to 5 .exist Figure 3 In the example, the X-axis is the scattering vector q, and the Y-axis is the scattering intensity I. Small-angle scattering can be used to measure the scattering vector q below The smaller the scattering vector q, the smaller the corresponding structure size. The larger the scattering vector q, the larger the corresponding structure size. In the range of scattering vector q of 0.04 to 0.06, these curves can correspond to the scattering characteristics of a single spherulite. Through software (SASView) analysis, the fractal dimension (D) of a single spherulite in each group can be obtained. m ) and radius of gyration (R g ). Regarding the aforementioned fractal dimension (D m ), each curve can be fitted with a regression line (such as Figure 4 and Figure 5 The absolute value of the slope of this regression line is the fractal dimension (D m ), can be used to evaluate the surface complexity of a single spherulite. For ease of understanding, Figure 4 and Figure 5 Further Figure 3 The curves in are extracted from the scattering vector q interval from 0.04 to 0.06 and presented in a single graph. Figure 4 and Figure 5 In each graph, each curve is presented as a solid line, and the straight line fitted to the curve is presented as a dotted line. Figure 4The curve of Comparative Example C1 can be fitted with a straight line L1, and the equation of the straight line L1 is y = -12.907x + 1.5305. The absolute value of the slope of the straight line L1 is 12.907, which is the fractal dimension (D) of Comparative Example C1. m ). The curve of Comparative Example C2 can be fitted with a straight line L2, and the equation of the straight line L2 is y = -12.071x + 1.4949. The absolute value of the slope of the straight line L2 is 12.071, which is the fractal dimension (D) of Comparative Example C2. m ). Next, please continue to refer to Figure 5 The curve of Example E1 can be fitted to a straight line L3, and the equation of the straight line L3 is y=-11.556x+1.4379. The absolute value of the slope of the straight line L3 is 11.556, which is the fractal dimension (D) of Example E1. m ). The curve of Example E2 can be fitted to a straight line L4, and the equation of the straight line L4 is y=-10.935x+1.3935. The absolute value of the slope of the straight line L4 is 10.935, which is the fractal dimension (D) of Example E2. m ). The curve of Example E3 can be fitted to a straight line L5, and the equation of the straight line L5 is y=-9.846x+1.2931. The absolute value of the slope of the straight line L5 is 9.846, which is the fractal dimension (D) of Example E3. m ). The curve of Example E4 can be fitted to a straight line L6, and the equation of the straight line L6 is y=-7.8727x+1.1399. The absolute value of the slope of the straight line L6 is about 7.873, which is the fractal dimension (D) of Example E4. m ).also, Figure 4 and Figure 5 R 2 is the variation between the fitted line and the curve. The closer it is to 1, the smaller the variation is, and the more consistent the fitted line and the curve are. g ), it can also be obtained through SASView under the relationship that complies with Guinier law. g It can also be called the particle's rotation radius. Through this parameter, we can know the range in which the spherulite can rotate in a space, so it can be defined as the radius of the single spherulite.

[0053] Based on the adjustments made in Table 2, the durability of each group was subsequently verified through cycle life tests under different conditions.

[0054] Table 3. Durability test

[0055]

[0056] R i, refers to the initial resistance value of the overcurrent protection element at room temperature. In addition, according to the volume resistivity formula ρ = R × A / L, R is the resistance value, L is the thickness, and A is the area. Based on this, R i Substitute into the formula to obtain the volume resistivity ρ i .

[0057] R 6000C1 , refers to the first resistance value of the overcurrent protection element after 6000 cycles of the first cycle life test mentioned above and cooling to room temperature. The conditions of the first cycle life test are 24V / 50A voltage / current applied for 10 seconds, and then turned off for 60 seconds as one cycle. This is repeated for 6000 cycles.

[0058] R 6000C2 , refers to the second resistance value of the overcurrent protection element after 6000 cycles of the second cycle life test mentioned above and cooling to room temperature. The conditions of the second cycle life test are 30V / 40A voltage / current applied for 10 seconds, and then turned off for 60 seconds as one cycle. This is repeated for 6000 cycles.

[0059] R 6000C3 , refers to the third resistance value of the overcurrent protection element after 6000 cycles of the third cycle life test mentioned above and cooling to room temperature. The conditions of the third cycle life test are 36V / 33A voltage / current applied for 10 seconds, and then turned off for 60 seconds as one cycle. This is repeated for 6000 cycles.

[0060] R 6000C1 / R i , R 6000C2 / R i and R 6000C3 / R i They are the first resistance jump ratio, the second resistance jump ratio and the third resistance jump ratio mentioned above. The resistance jump ratio can be used to evaluate the resistance recovery ability of the overcurrent protection element after multiple triggering. The lower the value, the better the ability of the overcurrent protection element to recover to a low resistance state.

[0061] Regarding the initial resistance value (R i ) and initial volume resistivity (ρ i ), there is no big difference between Examples E1 to E4 and Comparative Examples C1 and C2. Specifically, the initial resistance values ​​(R i ) is 0.1016Ω to 0.149Ω, and its volume resistivity (ρ i ) is 0.478Ω·cm to 0.701Ω·cm; while the initial resistance values ​​(R i) is 0.0879Ω to 0.0906Ω, and its volume resistivity (ρ i ) is 0.413Ω·cm to 0.426Ω·cm. However, after multiple triggering (such as the aforementioned cycle life test), Examples E1 to E4 can clearly show their advantages in resistance stability and durability. Compared with Comparative Examples C1 and C2, in Examples E1 to E4, the first resistance value (R 6000C1 ) is 0.1735Ω to 0.2839Ω, and the first resistance jump ratio (R 6000C1 / R i ) is 1.19 to 2.79, and both values ​​are significantly reduced, indicating that the overcurrent protection elements of Examples E1 to E4 can still recover to a relatively low resistance state after 6000 cycles of 24V / 50A voltage / current, and have excellent resistance stability. Then, the second cycle life test further increases the applied voltage value. Compared with Comparative Examples C1 and C2, in Examples E1 to E4, the second resistance value (R 6000C2 ) is 0.3093Ω to 0.4578Ω, and the second resistor jump ratio (R 6000C2 / R i ) is 2.07 to 4.5. Similarly, the numerical range of the two is still significantly reduced, indicating that the overcurrent protection elements of Examples E1 to E4 can still recover to a relatively low resistance state after 6000 cycles of 30V / 40A voltage / current, and have excellent resistance stability. In addition, in order to further distinguish the difference in service life (i.e. durability) between the embodiments and the comparative examples, the voltage value is increased to 36V in the third cycle life test. It can be seen from Table 3 that after the third cycle life test, the overcurrent protection elements of Comparative Examples C1 and C2 will be burned, so the corresponding third resistance value (R 6000C3 ) and the third resistor jump ratio (R 6000C3 / R i ). In the embodiments E1 to E4, the overcurrent protection element is not burned out after the third cycle life test and can continue to be repeatedly used in electronic products to play its protective function. In addition, the third resistance value (R 6000C3 ) is 0.4452Ω to 0.86Ω, and the third resistor jump ratio (R 6000C3 / R i ) is 3.03 to 8.46. From the results of the first cycle life test, the second cycle life test and the third cycle life test, it can be seen that reducing the spherulite surface complexity (i.e., D m ) and increase the spherulite radius (i.e. R g), which not only helps to improve the resistance stability of the overcurrent protection element, but also enhances its durability and can be used in electronic products that require higher withstand voltage values.

[0062] The technical content and technical features of the present invention have been disclosed as above, but a person skilled in the art with ordinary knowledge may still make various substitutions and modifications based on the teachings and disclosures of the present invention without departing from the spirit of the present invention. Therefore, the protection scope of the present invention should not be limited to those disclosed in the embodiments, but should include various substitutions and modifications without departing from the present invention, and be covered by the following claims.

Claims

1. An overcurrent protection element, comprising: an electrode layer having an upper metal layer and a lower metal layer; and A thermistor layer contacts the upper metal layer and the lower metal layer and is stacked therebetween, wherein the thermistor layer has a positive temperature coefficient characteristic and comprises: A polymer substrate comprising a fluorine-containing polymer, wherein the fluorine-containing polymer has a plurality of spherulites, and the fractal dimension of the surface of each spherulite is less than 12; and A conductive filler is dispersed in the high molecular polymer matrix to form a conductive channel of the thermistor layer. 2 . The overcurrent protection device as claimed in claim 1 , wherein the fractal dimension of each spherulite surface is between 7 and 12. 3 .

3. The overcurrent protection device according to claim 1, wherein each of the spherulites has a spherulite radius greater than 4. The overcurrent protection element according to claim 3, wherein the spherulite radius is between and between. 5 . The overcurrent protection device according to claim 1 , wherein based on 100% by volume of the thermistor layer, the fluorine-containing polymer accounts for 55% to 68%.

6. The overcurrent protection device according to claim 5, wherein the fluorine-containing polymer is selected from the group consisting of polyvinylidene fluoride, polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, perfluoroalkylene-modified tetrafluoroethylene, poly(chlorotri-fluorotetrafluoroethylene), difluoroethylene-tetrafluoroethylene polymer, tetrafluoroethylene-perfluorodioxole copolymer, difluoroethylene-hexafluoropropylene copolymer, difluoroethylene-hexafluoropropylene-tetrafluoroethylene terpolymer and any combination thereof. 7 . The overcurrent protection device according to claim 6 , wherein the fluorine-containing polymer consists of polyvinylidene fluoride and polytetrafluoroethylene. 8 . The overcurrent protection element according to claim 7 , wherein based on 100% by volume of the thermistor layer, polyvinylidene fluoride accounts for 56% to 62% and polytetrafluoroethylene accounts for 3% to 5%. 9 . The overcurrent protection device as claimed in claim 1 , wherein the conductive filler consists of carbon black. 10 . The overcurrent protection device according to claim 1 , wherein the thickness of the thermistor layer is 0.1 mm to 0.2 mm.

11. The overcurrent protection device according to claim 1, wherein the overcurrent protection device has a top surface area of ​​4 mm 2 Up to 16mm 2 .

12. The overcurrent protection device according to claim 1, wherein the overcurrent protection device has a first resistance jump ratio between 1 and 3, wherein: The overcurrent protection element has an initial resistance value; The overcurrent protection element has a first resistance value after being subjected to a 24V / 50A cycle life test for 6000 times and cooled to room temperature; and The first resistance value divided by the initial resistance value is the first resistance jump ratio.

13. The overcurrent protection device according to claim 1, wherein the overcurrent protection device has a second resistance jump ratio between 2 and 5, wherein: The overcurrent protection element has an initial resistance value; The overcurrent protection element has a second resistance value after being subjected to a 30V / 40A cycle life test for 6000 times and cooled to room temperature; and The second resistance value divided by the initial resistance value is the second resistance jump ratio.

14. The overcurrent protection element as claimed in claim 1, wherein the overcurrent protection element has a withstand voltage of 36V, whereby the overcurrent protection element can be tested for 6000 cycles at 36V / 33A without burning out.

15. The overcurrent protection device according to claim 1, wherein the overcurrent protection device has a third resistance jump ratio between 3 and 9, wherein: The overcurrent protection element has an initial resistance value; The over-current protection element has a third resistance value after being subjected to a 36V / 33A cycle life test for 6000 times and cooled to room temperature; and The third resistance value divided by the initial resistance value is the third resistance jump ratio.

Citation Information

Cited By

  • Composite current collector and lithium battery

    CN121123288A